(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
An old Indian traditional medical practice called Siddha developed in South India. The Lord typically serves as the source of the system. It is believed that Goddess Parvathi, represented by Lord Shiva, received the Siddha system’s knowledge from the Almighty, who then passed it on to Nandikeswara. Nandikeswara was appointed to set up for the framework to be spread in the midst of humankind thus, he obediently granted the information to Sage Agastya. Agastya gave all of the relevant information to his various disciples, who helped spread the system around the world. Diet and lifestyle play a significant role in both health and disease treatment, according to the Siddha medicine system. Pathiyam and Apathiyam refer to this Siddha medicine concept, which is essentially a rule-based system with a list of "dos and don’ts.” The aim of this review article is to explore the scientific literary evidence for the therapeutic usage of Panchadeepakini chooranam for (Silethuma Noi/Kaba Noi) as mentioned in Citta Vaittiya Tirattu and to assign effort to entity the pharmacological activity for the curative nature of the drug. Most of the raw drugs used for the preparation of Panchadeepakini chooranam have bronchodilatory activity, anti-tussive activity, anti-allergic activity, immunomodulatory activity, anti-histamine activity hence justifying its usage in respiratory illness.